﻿Hydraulic engineering of Drusinae larvae: head morphologies and their impact on surrounding flow fields - Ariane Vieira; Hendrik C. Kuhlmann; Johann Waringer; Carina Zittra; Simon Vitecek; Stephan Handschuh (Contributions to Entomology)
Body morphologies are significantly different amongst the members of the Drusinae subfamily. Aligned with such differences is the selective niche location chosen by many species from the subfamily. Typically, they live on the sediments of cold, well-oxygenated mountain streams from the Eurasian Region. However, each of the three evolutionary lineages (shredders, grazers and carnivorous filter feeders) inhabit different hydraulic locations according to their foraging behaviour. To investigate the relationship between the body morphology and the flow field near the body, we use Large Eddy Simulations to compute the flow past five different species of the subfamily. We selected species representing the three evolutionary lineages of the subfamily, Drusus alpinus Meyer-Dür 1875 from the shredders clade, D. bosnicus Klapálek 1899 and D. monticola McLachlan 1876 from the grazers clade and Cryptothrix nebulicola McLachlan 1867 and D. discolor (Rambur 1842) from the filter feeders clade. For the simulations, three-dimensional body shapes were reconstructed from X-ray micro CT data and exposed to a turbulent flow corresponding to water-depth and velocity data measured in the field. The total forces acting on each morphotype were found to be comparable. The lift coefficients computed and ranging from 0.07 to 0.17 are smaller than the drag coefficients which were found to range from 0.32 to 0.55. The local distribution of the skin-friction indicates flow-separation zones near the edges of the bodies, in particular, between the head and the pronotum, which are differently located according to each species. Moreover, we observe higher streamwise normal stresses upstream of the head of the filter feeder species. It is hypothesised that the upstream horseshoe vortex can lift up drifting food particles and transport these to the larvae’s filtering legs, thereby enhancing the encounter rates of particles with the filtering devices.